Manajemen Stratejik Pemanfaatan Teknologi Informasi dan Komunikasi untuk Peningkatan Mutu Pembelajaran SMK Ciledug Al Musaddadiyah dan SMKN 1 Garut - Partono Partono (Masoem University, 2020)
So far, in implementing school strategies, they tend not to utilize Information and Communication Technology (ICT), despite the availability of ICT resources available. Stages of strategic management are needed to generate the vision, mission, objectives, policy, program, budget, and procedures as well as control and evaluation process as an effort to utilize ICT to improve school quality. Based on the interpretation and the results of the study, it is concluded that schools have organized stages in strategic management that enable schools to have a quality profile. The impact of effective utilization of ICTs for schools is the achievement of effective school management, as per the National Education Standards, which is characterized by effective planning, implementation, control, and evaluation of school ICTs.The purpose of this study is to get a general description, describe, and reveal the Strategic Management of Information and Communication Technology Utilization to Improve the Quality of School Learning in Ciledug Al Musaddadiyah Vocational High School and Garut 1 Vocational High School, both on environmental analysis, strategic formulation, implementation and strategic evaluation. The research method used in this research is the case study method, because the problems studied occur in the place and situation of Ciledug Al Musaddadiyah Vocational School and Vocational High School 1 Garut. The use of case study models in this study is based on the consideration that to provide an overview of the strategic management activities of the use of ICTs carried out at vocational high schools with the ultimate goal of being able to improve the quality of school learning. Based on observations in the field of SMK 1 Garut and SMK Al Musaddadiyah Ciledug Garut is one of the public schools and private schools that have these advantages.